Practices and Environments of Collective Sleep in Twenty-First-Century Latin American Film - Zarza, Zaira (Intermédialités / Intermediality, 2023)
What do practices of sleep—or lack thereof—convey about power, social and class divides, and political structures in Latin American postcolonial societies? How does cinema represent and critique binaries such as conscious/unconscious, utopian/dystopian, individual/social, and private/public that are often associated with settings where sleep-wake cycles take place? In exploring these questions, this article analyzes practices and, more specifically, environments of collective sleep as affective landscapes and narrative tools in contemporary Latin American films. It draws from atmospheric family dramas in neoliberal Argentina and dark sci-fi comedies in post-socialist Cuba to examine embodied and em(bed)ded relations before, during, and after acts of sleeping, dreaming, and awakening.